2022
DOI: 10.1128/msystems.00991-21
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Functional Diversity Correlates with Species Diversity along a Temperature Gradient

Abstract: Only recently have microbial ecologists begun to assess quantitatively how microbial species diversity correlates with environmental factors like pH, temperature, and salinity. However, still, very few studies have examined how the number of distinct biochemical functions of microbial communities, termed functional diversity, varies with the same environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 65 publications
3
12
0
Order By: Relevance
“…Though the functional categories are different to those in FAPROTAX, both approaches suggest the potential of the midgut bacterial community to perform carbon, nitrogen, and energy metabolism. Consistently with other models [ 102 , 103 ], we observed that the functional trait abundances of the bacterial communities reflect the overall beta diversity, as samples cluster predominantly in a by-tissue pattern ( Fig 8 ). We detected a significant difference in methanol oxidation potential between the crop and midgut.…”
Section: Discussionsupporting
confidence: 90%
“…Though the functional categories are different to those in FAPROTAX, both approaches suggest the potential of the midgut bacterial community to perform carbon, nitrogen, and energy metabolism. Consistently with other models [ 102 , 103 ], we observed that the functional trait abundances of the bacterial communities reflect the overall beta diversity, as samples cluster predominantly in a by-tissue pattern ( Fig 8 ). We detected a significant difference in methanol oxidation potential between the crop and midgut.…”
Section: Discussionsupporting
confidence: 90%
“…Though the functional categories are different to those in FAPROTAX, both approaches suggest the potential of the midgut bacterial community to perform carbon, nitrogen, and energy metabolism. Consistently with other models [99,100], we observed how the functional trait abundances of the bacterial communities reflect the overall beta diversity, as samples cluster predominantly in a by-tissue pattern. We detected a significant difference in methanol oxidation potential between the crop and midgut.…”
Section: Discussionsupporting
confidence: 90%
“…This tendency is also indicated in Fig. S3 of Ruhl et al 2022, where log-transformed data, being less dense with smaller TR levels, leads to overestimation. As our focus is on the initial phases of microbial extinctions and their impacts on ecosystem multifunctionality, the bias introduced by severe extinctions (e.g., 95% reduction of the maximum ASV richness) does not significantly compromise the efficacy of the power-law regression method for assessing multifunctional redundancy.…”
Section: Setting For Asv-extinction Simulations and Fitting Of Power-...supporting
confidence: 57%
“…Second, the comparison of redundancy exponents between this study and past studies (21,29) provides insights into the robustness of the proposed method and offers cautions for its application to other systems. The exponent (a) values estimated in Miki, Yokokawa and Matsui (2014) ranged from 0.55 to 0.75, but these may have been overestimated as they were derived from pseudo-communities containing a single strain from each genus.…”
Section: Advancing Methodology: Underexplored Aspects and Future Dire...mentioning
confidence: 82%